succession - Grigoryeva, Elena (project baikal, 2021)
Does new always mean the best? Throughout  the  last  century people had been actively  trying  to  invent  and  build  a  new world.  A  world  without  old  or  obsolete things.  The  end  of  the  millennium  gave rise  to  an  illusion  that  all  achievements, disasters and confrontations of the previous ten centuries were left behind. But the new century has already brought so drastic changes that the attitude toward the past is no longer the same. The larger the wave of  the  new  becomes,  the  more  precious looks the succession, or the continuity of the past in the present.Is  it  pure  coincidence  that  the  English words “succession” and “success” have the same  root? The  Ise Shrine  in Japan  is  rebuilt every 20 years because two previous generations of craftsmen are still alive at the time of each reconstruction. The tradition does not change. The technology, the aesthetic principles, the manner of understanding and feeling of beauty are passed from hand to hand.We have  frequently  referred  to  the period of  creative  rise  in  the middle  of  the  last century,  to  the  phenomenon  of  the  “sixtiers”. Like the modernism  itself, Siberian brutalism  opposed  the  classical  cannons, but  today  its  audacious  large-scale  solutions  look  like  a  direct  continuation  of the  centuries-old  development  of  architecture. Today’s rebirth of  interest  in brutalism  is not accidental. We believe  in  its recovery, of course, on a new level of comprehension and in new forms.Indeed, if the main function of the state in the 21st  century  is  to provide  conditions for human self-realisation with the use of cultural and historical  identity,  it  is  time to speak about SUCCESSION.
Keywords: sixtiers; succession; identity